2021
DOI: 10.3389/fped.2021.697390
|View full text |Cite|
|
Sign up to set email alerts
|

Age-Related Differences in the Expression of Most Relevant Mediators of SARS-CoV-2 Infection in Human Respiratory and Gastrointestinal Tract

Abstract: Background: Clinical features of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection seem to differ in children compared to that in adults. It has been hypothesized that the lower clinical severity in children could be influenced by differential expression of the main host functional receptor to SARS-CoV-2, the angiotensin-converting enzyme 2 (ACE2), but data are still conflicting. To explore the origin of age-dependent clinical features of coronavirus disease 2019 (COVID-19), we comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 40 publications
(63 reference statements)
2
27
1
2
Order By: Relevance
“…Coronavirus disease 2019 (COVID-19) is an ongoing pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Atzrodt et al, 2020 ). Gastrointestinal (GI) symptoms (such as diarrhea, nausea, vomiting, anorexia and abdominal pain) are commonly presented by COVID-19 patients, since human enterocytes express high level of angiotensin-converting enzyme-2 (ACE2) receptor, and other cell components for SARS-CoV-2 binding and replication ( Berni Canani et al, 2021 , Chen et al, 2020 , Zang et al, 2020 ). The spike (S) protein of SARS-CoV-2 binds to the host functional ACE2 receptor through its receptor-binding domain.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is an ongoing pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Atzrodt et al, 2020 ). Gastrointestinal (GI) symptoms (such as diarrhea, nausea, vomiting, anorexia and abdominal pain) are commonly presented by COVID-19 patients, since human enterocytes express high level of angiotensin-converting enzyme-2 (ACE2) receptor, and other cell components for SARS-CoV-2 binding and replication ( Berni Canani et al, 2021 , Chen et al, 2020 , Zang et al, 2020 ). The spike (S) protein of SARS-CoV-2 binds to the host functional ACE2 receptor through its receptor-binding domain.…”
Section: Introductionmentioning
confidence: 99%
“…In a first set of experiments, we investigated the direct effect of FBA on the expression of the main molecular players of SARS-CoV-2 infection: ACE2 , TMPRSS2 , NRP1 [ 4 , 5 , 6 , 7 ] and inflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…We found that FBA was able to modulate the main players of SARS-CoV-2 infection: ACE2 , TMPRSS2 and NRP-1 [ 4 , 5 , 6 , 7 ] and inflammatory cytokines IL-15 , MCP-1 and TNF-α in the human intestine and enterocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations